The FTO A/T polymorphism and elite athletic performance: A study involving three groups of European athletes - Eynon, N.; Nasibulina, E. S.; Banting, L. K.; Cieszczyk, P.; Maciejewska-Karlowska, A.; Sawczuk, M.; Bondareva, E. A.; Shagimardanova, R. R.; Raz, M.; Sharon, Y.; Williams, A. G.; Ahmetov, I. I.; et al. (PLOS ONE, 2012)
The FTO A/T polymorphism (rs9939609) is a strong candidate to influence obesity-related traits. Elite athletes from many different sporting disciplines are characterized by low body fat. Therefore, the aim of this study was to assess whether athletic status is associated with the FTO A/T polymorphism. Subjects and Methods: A large cohort of European Caucasians from Poland, Russia and Spain were tested to examine the association between FTO A/T polymorphism (rs9939609) and athletic status. A total of 551 athletes were divided by type of sport (endurance athletes, n = 266 vs. sprint/power athletes, n = 285) as well as by level of competition (elite-level vs. national-level). The control group consisted of 1,416 ethnically-matched, non-athletic participants, all Europeans. Multinomial logistic regression analyses were conducted to assess the association between FTO A/T genotypes and athletic status/competition level. Results: There were no significantly greater/lesser odds of harbouring any type of genotype when comparing across athletic status (endurance athletes, sprint/power athletes or control participants). These effects were observed after controlling for sex and nationality. Furthermore, no significantly greater/lesser odds ratios were observed for any of the genotypes in respect to the level of competition (elite-level vs. national-level). Conclusion: The FTO A/T polymorphism is not associated with elite athletic status in the largest group of elite athletes studied to date. Large collaborations and data sharing between researchers, as presented here, are strongly recommended to enhance the research in the field of exercise genomics.